2011
DOI: 10.1093/europace/eur190
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of percutaneous implantation of transapical endocardial left ventricular pacing electrode for cardiac resynchronization therapy

Abstract: Failure of coronary sinus lead implantation for resynchronization therapy requires alternative approaches. For such events we have developed a transapical implantation technique as a feasible alternative. We report the outcome of this technique and its evolution from a minithoracotomy to a percutaneous approach. Twenty patients underwent alternative resynchronization therapy with transapical endocardial left ventricular (LV) pacing lead implantation in a multicentre, international study between October 2007 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
1
16
1
Order By: Relevance
“…Two randomized studies have demonstrated the non‐inferiority of open‐chest access vs transvenous approach, in addition to several other non‐randomized studies …”
Section: Discussionmentioning
confidence: 99%
“…Two randomized studies have demonstrated the non‐inferiority of open‐chest access vs transvenous approach, in addition to several other non‐randomized studies …”
Section: Discussionmentioning
confidence: 99%
“…In the sensitivity analyses, it was even higher at 3.29–4.2 per 100 patient‐years. This is of relevance, as this analysis included larger studies with better quality outcomes data . These findings are contrary to those of Gamble in a recent meta‐analysis of this subject.…”
Section: Discussionmentioning
confidence: 78%
“…(2011) is a subgroup of Kis et al. (2017) in which NYHA and LVEF data was available . CRT = cardiac resynchronization therapy; LVEF = left ventricular ejection fraction; NYHA = New York Heart Association.…”
Section: Resultsmentioning
confidence: 99%
“…However, intentional left ventricular endocardial lead placement via a transseptal puncture or the trans-apical route is feasible and results in ventricular remodeling. 9,10 Multiple studies demonstrate a hemodynamic benefit to endocardial left ventricular pacing in comparison with epicardial pacing. 11,12 This could be explained by the more physiogenic endocardial to epicardial depolarization and by the existence of the ability to select the pacing site with a deflectable catheter.…”
mentioning
confidence: 99%